Effects of training method and computer anxiety on learning performance and self-efficacy. - Chou, H.-W. (Computers in Human Behavior, 2001)
A study was conducted to compare the effects of training method and computer anxiety on learners' computer self-efficacy and learning performance. Findings indicated that the behavior-modeling training approach yielded consistently better performance and higher computer self-efficacy. In addition, it was observed that the significant two-way interaction confirmed the importance of person-situation adaptation and that the adaptation is task-dependent. It was concluded that the findings add to an expanded knowledge of the factors that influence learning performance and self-efficacy, and that they have important implications for the management of information systems.